Identification of novel diagnostic markers for sinonasal undifferentiated carcinoma. Issue 8 (1st April 2019) - Takahashi, Yoko; Gleber‐Netto, Frederico O.; Bell, Diana; Roberts, Dianna; Xie, Tong‐Xin; Abdelmeguid, Ahmed S.; Pickering, Curtis; Myers, Jeffrey N.; Hanna, Ehab Y.
Abstract: Background: Sinonasal undifferentiated carcinoma (SNUC) is a rare, highly aggressive cancer. It is often difficult to determine whether SNUC is a distinct pathologic entity with poorly differentiated neuroendocrine features or it represents an undifferentiated tumor of squamous lineage. Also, reliable histopathologic markers that distinguish SNUC from poorly differentiated sinonasal squamous cell carcinoma (SNSCC) are lacking. Therefore, identification of new diagnostic molecular markers for SNUC is needed. Methods: Treatment‐naïve tumor specimens obtained from 15 SNUC and 6 SNSCC patients were used. Gene expression analysis was performed using an oncology panel. Results: An unsupervised cluster analysis divided the patients into the one with only SNUCs and the one with mainly SNSCCs. Of 132 differentially expressed genes, 7 genes completely distinguished SNUCs from SNSCCs. SNUCs were enriched in sets of genes related to DNA repair, synthesis/replication, and cell division. Conclusions: Our study identified new diagnostic markers and potential therapeutic targets for SNUC.